(untitled) - Womack, James P. (New York, 1990)
Japanese companies are sweeping the world, and the Japanese auto industry soars above the competition. Drawing on their in-depth study of the practices of ninety auto assembly plants in seventeen countries and their interviews with individual employees, scholars, and union and government officials, the authors of this compelling study uncover the specific manufacturing techniques behind Japan's success and show how Western industry can implement these innovative methods. The Machine That Changed the World tells the fascinating story of "lean production," a manufacturing system that results in a better, more cost-efficient product, higher productivity, and greater customer loyalty. The hallmarks of lean production are teamwork, communication, and efficient use of resources. And the results are remarkable: cars with one-third the defects, built in half the factory space, using half the man-hours.
Keywords: Công nghiệp ô tô và thương mại,Automobile industry and trade; Nhật Bản,Japan